The Pictorial Means of Death and Life in the View of Gibran Khalil Gibran: A Critical Artistic Study - Khan, Yahya; Zia Uddin (Journal of Islamic and Religious Studies, 2016)
The concept of imagery plays an important role in literacy, critical and rhetorical studies. Different research studies describe the reality of imagery its role and methods of its formulation in literary work. Imageries are among those literary tools, through which writers share their experiences. The writer uses different literary tools to formulate imagery and to share their feelings with readers. These tools are simile, metaphor, sensuousness, personification and oxymoron etc. khalil Jubran was among those writers who frequently used imagery in his work to reflect his inner feelings in a better way. This research study was focused only on the use of imagery tools in his work for the formulation of life and death.